Method of compensations evaluation in Ulaanbaatar - Nyamsuren, O; Gerelkhuu, T (Mongolian Journal of Agricultural Sciences, 2014)
It is significant to make evaluation of ger area, determine market price of compensation, process evaluation procedure of compensation evaluation, transfer land for need of capital city and determine compensation using methods in international evaluation standards of land and cadastre evaluations methods. Land of Ulaanbaatar city is divided in 65 regions for evaluation, market price per a square meters of land is 156063 Tugrugs. In making adjustment on regional market price using factors to impact on land in accordance with certain methods, price of land per square meter reached 220049 Tugrugs. DOI: http://dx.doi.org/10.5564/mjas.v11i2.233 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.129-132